Unlocking Academic Vocabulary in Grade 3: The Role of Handwriting - Roessingh, Hetty; Nordstokke, David; Mir-Orefice, Aurelia (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2025)
This mixed methods inquiry seeks research insights into the inter-relationships among handwriting, quality writing outcomes, fluency and various indices of vocabulary use visible in writing samples of 216 Grade 3 students in response to an expository prompt. The findings highlight the connection among these variables most importantly the role of handwriting. Sustained attention on direct teaching of handwriting that will in turn increase fluency and improve retrieval of vocabulary is warranted. Secondly, instructional attention is warranted in developing academic vocabulary especially for linguistically vulnerable young learners.